Pelatihan Asertif Bagi Remaja: Upaya Preventif Tindakan Kekerasan di Sekolah - Salau, Triati; Keo, Glorius Deonatus; Labre, Benediktus; Fanggitasik, Deslien Dolorosa (Warta LPM, 2023)
Students who are victims of violence at school can experience depression, anxiety, low self-esteem, and even suicide. One way to avoid further confrontation and serious impacts is that students at SMP Negeri 10 Takari need to receive assertive training. The aim is to increase students' self-awareness of the violence they experience, then they can make practical, solution and effective preventif efforts to avoid, dispel, reject and anticipate bad situations through assertive training. The methods used are 1) Assessment Study, 2) Assertive Training with cognitive restructuring strategies, role playing, self talk, relaxation, modeling and 3) Monitoring & Evaluation. The results, 1) as many as 74% (37 students) had low self-concept, self-esteem and self-confidence. Students' attitudes and responses to violence tend to be aggressive and submissive. There are various forms of violence experienced by students. 2) Cognitive restructuring strategies can increase students' understanding and positive self-acceptance. Role playing, self-talk and relaxation activities in groups can minimize aggressive and submissive attitudes to become assertive verbally as well as forming a firm and courageous attitude in determining an assertive attitude. 3) Monitoring and evaluation results show an 11% increase in students' understanding of self-concept, self-esteem and self-confidence. A total of 22 students showed a brave attitude to complain/report, 41 students responded to situations of violence by having the courage to speak out verbally, 20 students also no longer panicked and were anxious but became calmer and did not fight back against the perpetrator but refused and pushed back firmly. Assertiveness training can provide positive self-concept understanding for students to identify various forms of violence and their impacts, as well as being able to apply assertive attitudes appropriately.